Transmission Potential of Human Monkeypox in Mass Gatherings. (25th October 2022) - Sypsa, Vana; Mameletzis, Ioannis; Tsiodras, Sotirios
Abstract: Since May 2022, a large number of monkeypox cases have been reported in Europe, the United States, and other nonendemic settings. Taking into account the strict measures implemented due to the coronavirus disease 2019 pandemic and the desire of people to reclaim what is perceived as lost time, mass gatherings this summer were highly attended. Based on data for the secondary attack rate among unvaccinated contacts from endemic countries, we estimate that, on average, >1 secondary case is anticipated per infectious person if he/she has a high number of group contacts (>30) or >8 close contacts. Although the role of group contacts in mass gatherings is uncertain (less likely to involve physical contact, shorter duration), close contacts associated with the event (eg, intimate/sexual contact with other attendees) might be the amplifying event. Enforcing awareness, early recognition, and engaging affected populations in the monkeypox response are important to control transmission. Abstract : After two years of COVID-19 restrictions, mass gatherings this summer will be highly attended. We estimate more than one secondary monkeypox case per infectious person depending on his/her contacts in such events. Early recognition and engaging affected populations are needed.